STRENGTHENING THE MORAL BELIEFS STUDENTS OF ISLAMIC BASIC EDUCATION IN THE ERA OF DIGITALIZATION - Masbur Masbur (PIONIR: JURNAL PENDIDIKAN, 2024)
It's an era of evolution where people easily access information through digital networks. This digital era makes it easier and faster to search for knowledge, information and communication in education. Apart from having a positive impact, this digital era also has negative impacts; including making human’s individual creatures. Strengthening these moral beliefs makes people more religious and moral in living their lives. Many people have ignored moral beliefs, even though the issue of moral beliefs cannot be taken lightly, because beliefs are the foundation of life for Muslims and morals are the realization of faith itself. This study is an effort to motivate or empower teenagers and optimize their abilities in facing the era of digitalization. This research is to find out how to strengthen the beliefs and morals of Islamic teenagers in the digital era. The research results were obtained from a literature study regarding moral education in the digital era. The research results were obtained by providing various guidance and knowledge about Islamic teachings correctly and guided by the Qur’an and hadith. Moral belief education can also make people who can withstand the test of responding to the current developments in the digital world.Keywords: Strengthening; Moral beliefs; Era of Digitalization